Effect of propolis extract on hematotoxicity and histological changes induced by Salmonella enterica serovar Typhimurium in BALB/c mice - Kalia, Preeti; Kumar, Neelima R; Harjai, Kusum (Archives of Biological Sciences, 2016)
Typhoid fever, a life-threatening disease, causes several pathological changes due to the involvement of one or more organs. In the present study, the effect of typhoid on hematological indices and spleen histology in infected mice were investigated. The ameliorative efficacy of the ethanolic extract of propolis was tested and compared with treatment with the typhoid drug,cefixime. BALB/c mice were divided into six groups:group1 was the normal control, group 2 was infected with Salmonella enteric serovar Typhimurium, group 3 was Salmonella infected and treated with cefixime, groups4 and 5 were Salmonella-infected mice treated with 100mg and 300mg of propolisrespectivelyandgroup6 was given only 300 mg propolis without infection. Mice were sacrificedafter completion of treatment and examination of spleenhistology and hematological studies were performed. Significant differences were observed in the propolis-treated group of mice as compared to the infected group without antibiotic, further confirming the ameliorative effect of propolis on Salmonella enterica serovar Typhimurium-induced toxicity in mice.